Urgensi Peningkatan Softskill pada Mahasiswa dalam Upaya Mempersiapkan Masa Depan - Dine Fitriana; Arbaiyah Yusuf; Dewi Chintia Cahya Ningrum; Anisya Putri Nur Marsanti (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2023)
This article discusses the urgency of improving soft skills in students in preparing for the future The purpose of writing this article is to make students aware of the importance of developing soft skills for their future in the world of work. because one's success is not only determined by hard skills but also by the ability to manage oneself and others. This article also highlights the lack of serious attention to developing soft skills in the learning process in higher education, which tends to emphasize the development of hard skills. This research uses a library research design. This approach utilizes related literature to collect information, analyze, and synthesize the urgency of soft skills for the future of students. The main data source in this research is scientific literature contained in various sources such as academic journals, textbooks, scientific articles, and official publications. The literature used includes empirical research, related theories, and recent findings related to soft skills and their impact on the future of students. Researchers analyzed literature data related to the focus of the research, namely regarding the urgency of improving soft skills in students in an effort to prepare for the future. Qualified soft skills are needed because they can determine the direction of the utilization of hard skills. Good soft skills can be a decisive factor in future life, helping students support academic and non-academic grades, and achieve a balance between work and personal life.